PERENCANAAN TROTOAR DALAM RANGKA PENINGKATAN KEAMANAN DAN KESELAMATAN PEJALAN KAKI - Suryobuwono, Abdullah Ade; Ricardianto, Prasadja (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2017)
A safe, convenient, and comfortable pedestrian network in the Kebon Nanas area is an important component that should be provided to improve the effectiveness of citizen mobility. Currently the availability of pedestrian network has not been able to meet the needs of the community both in terms of quantity and standard provision. The purpose of this research is to identify the need for revitalization of pavement in the area around IPN, Kebon Nanas East Jakarta. The approach method used in this research is descriptive quantitative analysis through direct measurement method in the field by Traffic Counting (TC) for vehicles and pedestrians, through which the study is reviewed based on development criteria. Sampling was conducted on eight points. The conclusions of this study are (1) the traffic volume in the vicinity of the IPN road is high enough for a community road class, while the pavement capacity is not standardized, thus affecting the safety and safety of pedestrians; (2) Based on field measurements, the number of pedestrians is very minimal,Â  2 persons/ minute/ meter, but it is necessary to revitalize to obtain adequate capacity according to the volume of pedestrians by considering safety and security; (3) Planning of pedestrian facility requirement in IPN and surrounding roads includes green lines, lighting, seating, safety fences, garbage cans, markers, shophouses and traffic signs.